PENGARUH MODEL PEMBELAJARAN TERHADAP KETERAMPILAN DESAIN DAN PRESTASI BELAJAR SISWA SMK NEGERI 4 DI KOTABENGKULU - Emmy Hasmiri; Riyanto (UNIB Press, 2022)
This study aims to see the effect of the Project Based Learning (PjBL) model on design skills and student achievement of SMK Negeri 4 in Bengkulu City. The type of research conducted is quantitative research with quasi-experimental research methods (quasi-experimental), the research design used is quasi- experimental. The population in this study were students of SMKN 4 in Bengkulu City in class XI of Software Engineering (RPL) expertise. The sample used by the author is probability sampling XI RPL 1 and XI RPL 2. Testing the hypothesis using two-way ANOVA analysis and t-test. Based on the analysis obtained, it can be concluded that (1) the learning achievement of the group of students who use the Project Based Learning (PjBL) learning model is higher than the students who use the conventional learning model, (2) the learning design skills of students who use the Project Based Learning learning model (PjBL) is higher than the group of students who use conventional learning models. It is shown by the difference in the average design skills and student achievement using the Project Based Learning (PjBL) Model and the Conventional Learning Model.